Survivin and Telomerase as Radiotherapeutic Response Predictors of Subjects with Stage IIIB Cervical Squamous Cell Carcinoma - Fitriyadi Kusuma; Andrijono Andrijono; Ani Retno Prijanti; Laila Nuranna; Sri Mutya Sekarutami; Bambang Sutrisna; Ferry Sandra (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Cervical cancer is one of the most prevalent cancers in women. Even with similar clinicopathologic features, radiotherapy outcomes are still vary among patients. This research was conducted to measure radiotherapy responses on cervical cancer patients by using Survivin, Telomerase and Cytochrome C.METHODS: Subjects who matched the criteria were selected and requested to fill questionnaires. Subjects were then evaluated with magnetic resonance imaging (MRI) pre- and post-3D conformal radiotherapy. Histopathological study was conducted using resected tumors to determine the differentiation type. Enzyme-linked Immunosorbent Assays for detection of Survivin, Telomerase and Cytochrome C was performed using the resected tumors as well.RESULTS: There were 76 patients in this study. Mean ofage was 50 and diameter of tumor size was 5.35 cm. Mean levels of Survivin, Telomerase and Cytochrome C were 632.82 pg/mL, 5.59 pg/mL and 204.75 ng/mL, respectively. There were significant correlations between radiotherapy response and Survivin (p=0.041) or Telomerase (p=0.022). Subjects with lower Survivin level (<932 pg/mL) had higher 1-year survival rate (63%) than subjects with higher Survivin level (50%). Similar results were obtained for subjects with lower Telomerase level (<5.75 pg/mL), who had higher 1-year survival rate (60%) than subjects with higher Telomerase level (43%).CONCLUSION: Since radiotherapy response is significantly correlated with Survivin and Telomerase levels and subjects with lower Survivin or Telomerase level have higher 1-year survival rate, it can be suggested that Survivin and Telomerase could be potential predictors of radiotherapeutic response for subjects with stage IIIB cervical squamous cell carcinoma.KEYWORDS: cervical cancer, radiotherapy Survivin, Telomerase, Cytochrome C